Tingkat kelangsungan hidup Trepang Benang (Bohadschia marmorta) dengan metode transverse-fission di perairan alam dan pada wadah terkontrol - Rondonuwu, Yonatan Y.; Sambali, Hariyani; Sinjal, Hengky J.; Kusen, Diane J.; Kalesaran, Ockstan Y.; Pratasik, Silvester B. (Universitas Sam Ratulangi, 2022)
This research was conducted to examine the survival and regeneration success rate of the Brown Sandfish (Bohadchia marmorata) using the Transverse-fission method in containers placed in nature and controlled. This research was conducted Â from June to July 2021, in Bahoi Village, West Likupang, North Minahasa. This research used the Transverse-fission method, in which B. marmorata was tied using a rubber band until cleavage occurred. The container used is a basket covered with a net as many as 6 units, each of which is insulated in the middle so that it becomes 12 parts. Individuals who have been tied, then observed for changes shortly after the binding is done until the individual is separated (every 1 - 2 hours), followed by observing the survival and regeneration of separate body parts (every 6 hours). The results of the study were then analyzed using SPSS 22 version with T-test. Â Based on the results of the research, the survival and regeneration success rate of B. marmorata using the Transverse-fission method placed in containers in natural waters was significantly different from that of B. marmorata placed in controlled containers, where the total survival rate of B. marmorata placed in in controlled containers reached 100% while the total survival rate of B. marmorata placed in natural waters only reached 3.33%.Â